2020
DOI: 10.1088/1757-899x/889/1/012019
|View full text |Cite
|
Sign up to set email alerts
|

Effect of bias voltage on the texture of the TiN and ZrN coatings deposited by vacuum ion-plasma method

Abstract: An X-ray diffraction method was used to study the formation of the crystallographic texture of vacuum ion-plasma TiN and ZrN coatings depend on the bias voltage on the substrate. It is shown that, at high values of the bias voltage (-100 V), a pronounced texture forms in TiN coatings and a two-component (111) + (113) texture in ZrN coatings. A decrease of the bias voltage to –10 V leads to a twofold increase in the hardness of the coatings, a non-texture state of TiN, and a weakening of the texture of ZrN coat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
2
2
0
Order By: Relevance
“…When comparing the productivity during drilling with a P6M5 steel tool, it is shown that the number of holes drilled with an uncoated drill is 47 when using a drill with TiN coating -88 holes, when using a drill with TiAlN coating -246 holes. That is, coating increases the productivity of the tool by 2-5 times, which is confirmed by the work of other authors [3,6,[13][14][15][16]20].…”
Section: Determination Of Mechanical Properties Of Coatingssupporting
confidence: 79%
See 2 more Smart Citations
“…When comparing the productivity during drilling with a P6M5 steel tool, it is shown that the number of holes drilled with an uncoated drill is 47 when using a drill with TiN coating -88 holes, when using a drill with TiAlN coating -246 holes. That is, coating increases the productivity of the tool by 2-5 times, which is confirmed by the work of other authors [3,6,[13][14][15][16]20].…”
Section: Determination Of Mechanical Properties Of Coatingssupporting
confidence: 79%
“…Changing the flow rate of nitrogen into the working chamber stimulates a decrease in the intensity of reflexes ( 200) and (220) for the distance "target-substrate" Ls-c 100 and 50 mm, respectively. From the X-ray diffraction data, the values of the parameters of the crystal lattice of the experimental samples 4.22-4.25 Å correlate well with the data for work [14].…”
Section: Study Of Tin Coatingssupporting
confidence: 70%
See 1 more Smart Citation
“…Such structure is typical for deposited TiN. It is characterized by the (111) texture component predominance [19]. In growth process, the deposited atoms diffuse over the surface until they enter the low-energy lattice sites and are included in the growing coating.…”
Section: Cross-section Coatings Structurementioning
confidence: 99%